2021
DOI: 10.1088/1755-1315/762/1/012064
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of pathogen mastitis in cow’s milk from Cicurug, Sukabumi, West Java, Indonesia

Abstract: Mastitis is a complex disease in cattle that it involves interactions between management practices and infectious agents. The common microorganisms causing mastitis are bacteria, besides this disease can be caused by mycoplasma, algae, and yeast. Pathogen microorganisms in milk can be obtained from cattle, human hands, equipment and the environment. This study aims to analyze the metagenomic of pathogen mastitis in cow’s milk from Cicurug, Sukabumi, West Java. ZymoBIOMICSTM DNA Miniprep Kit was used for genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Bacteria of the genus Ignavigranum are also known to cause mastitis and are associated with a subclinical form [ 67 , 68 ]. This was confirmed in a metagenomics study of milk samples of cows with subclinical mastitis that revealed the composition of the microbiome, in which a predominant bacterial genus was Ignavigranum [ 67 ]. Chryseobacterium is a Gram-negative bacterium that can promote pasteurized milk spoilage and recontamination, reducing milk quality [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria of the genus Ignavigranum are also known to cause mastitis and are associated with a subclinical form [ 67 , 68 ]. This was confirmed in a metagenomics study of milk samples of cows with subclinical mastitis that revealed the composition of the microbiome, in which a predominant bacterial genus was Ignavigranum [ 67 ]. Chryseobacterium is a Gram-negative bacterium that can promote pasteurized milk spoilage and recontamination, reducing milk quality [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the subclinical mastitis group, we observed an increase in the abundance of Aerosphaera after antibiotic treatment compared with that before treatment; this bacterial genus was previously identified by Kusumawati et al . [ 67 ] in the milk of cows with subclinical mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…While this approach can provide information on taxonomic composition, metagenomics can go beyond this application and provide insight into both species and subspecies diversity and functional potential by examining the gene sequences that encode for proteins or functional RNAs (e.g., mRNAs and noncoding RNA). A handful of studies have utilized metagenomic sequencing to characterize the composition of the milk microbiome in bovine ( Bhatt et al, 2012 ; Patel et al, 2017 ; Kusumawati et al, 2021 ) and human ( Jiménez et al, 2015 ; Kordy et al, 2020 ; Seferovic et al, 2020 ; Olshan et al, 2021 ) milk but very few have interrogated the functional potential of the microbial communities. Metagenomic deep sequencing was used to compare the microbiomes of milk obtained from cows with clinical mastitis and healthy control cows where functional annotation of the metagenomic sequences was performed to identify differences in metabolic pathways ( Hoque et al, 2019 ).…”
Section: Sequencing-based Omics Approachesmentioning
confidence: 99%